KAJIAN HUBUNGAN KONDUKTIVITAS LISTRIK DENGAN KONSENTRASI PADATAN TERLARUT PADA AIR PERMUKAAN - Fadhilah Irwan; Afdal Afdal; Indah Arlindia (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
A study to determine relationship between the electrical conductivity and total dissolved solid (TDS) in three types of surface water (sea, river and lake water) has been conducted. Sea water samples were taken on Padang beach, river water samples were taken on Batang Arau river and lake water samples on Diatas lake of Alahan Panjang. At each location, water samples were taken at six points at every 500 m distance. Sea water samples were taken at three points near the tourist attractions and at three points near the seaside. River water samples were taken at two points at upstream, midstream and downstream of the river respectively. Lake water samples were taken from the lake sides towards the middle of the lake. TDS value was determined by using gravimetry method and electrical conductivity values measured by conductivity meter. The average value of TDS of sea water is 23886.7 mg/l, the river water is 1873.3 mg/l and the lake water is 546.7 mg/l. The average value of the electrical conductivity of sea water is 177.9 Î¼S/cm, the river water is 139.1 Î¼S/cm and the lake water is 80.6 Î¼S/cm. TDS relationship with the electrical conductivity of the sea water can not be determined because of TDS values are oscillated with electrical conductivity. TDS relationship with the electrical conductivity is linear at small electrical conductivity value and it is not linear at high electrical conductivity value for the water samples of the river and the lake. The best model for the relationship between TDS and the electrical conductivity of the river and lake Diatas water are the second degree polynomial models with correlation coefficient of 0.9506 and 0.9896 respectively. TDS and electrical conductivity values of Maninjau water lake have linier correlation coefficient betweeen 0.0664 and 0.4972 but still show linear trends. Keywords: electrical conductivity, gravimetry, temperature, Total Dissolved Solid (TDS).